Narrative Authority, Paratext, and Identity in R. F. Kuang’s Yellowface - Nadira Puškar Mustafic (Asiatic: IIUM Journal of English Language and Literature, 2026)
In this paper, I use a narratological approach to analyse the use of metafiction, untrustworthy first-person narration, and paratext in R.F. Kuang’s Yellowface (2023). The novel’s self-referential highlighting of authorship as a constructed act of performance places it in the context of metafiction, as defined by Patricia Waugh and Linda Hutcheon. Wayne C. Booth, James Phelan, and Greta Olson help explain the degrees and effects of unreliable narration in the novel. June Hayward, its central character, transforms from a first-person unreliable narrator into an untrustworthy one. According to Gérard Genette, paratext, or material surrounding stories, influences how they are received and may destabilise their narrative authority. Yellowface exposes how the publishing industry and digital discourse shape the circulation of racialised narratives in the novel. Together, these perspectives show that Yellowface presents narrative authority as a product of form, institutional mediation, and reader response.